Chromosome-scale genomics, metabolomics, and transcriptomics provide insight into the synthesis and regulation of phenols in Vitis adenoclada grapes - Cheng, Guo; Wu, Daidong; Guo, Rongrong; Li, Hongyan; Wei, Rongfu; Zhang, Jin; Wei, Zhiyong; Meng, Xian; Yu, Huan; Xie, Linjun; Lin, Ling; Yao, Ning; et al. (Frontiers in Plant Science, 2023)
Vitis adenoclada is a wild grape unique to China. It exhibits well resistance to heat, humidity, fungal disease, drought, and soil infertility. Here, we report the high-quality, chromosome-level genome assembly of GH6 (V. adenoclada). The 498.27 Mb genome contained 221.78 Mb of transposable elements, 28,660 protein-coding genes, and 481.44 Mb of sequences associated with 19 chromosomes. GH6 shares a common ancestor with PN40024 (Vitis vinifera) from approximately 4.26–9.01 million years ago, whose divergence occurred later than Vitis rotundifolia and Vitis riparia. Widely-targeted metabolome and transcriptome analysis revealed that the profiles and metabolism of phenolic compounds in V. adenoclada varieties significantly were differed from other grape varieties. Specifically, V. adenoclada varieties were rich in phenolic acids and flavonols, whereas the flavan-3-ol and anthocyanin content was lower compared with other varieties that have V. vinifera consanguinity in this study. In addition, ferulic acid and stilbenes content were associated with higher expressions of COMT and STSs in V. adenoclada varieties. Furthermore, MYB2, MYB73-1, and MYB73-2 were presumably responsible for the high expression level of COMT in V. adenoclada berries. MYB12 (MYBF1) was positively correlated with PAL, CHS, FLS and UFGT.Meanwhile, MYB4 and MYBC2-L1 may inhibit the synthesis of flavan-3-ols and anthocyanins in two V. adenoclada varieties (YN2 and GH6). The publication of the V. adenoclada grape genome provides a molecular foundation for further revealing its flavor and quality characteristics, is also important for identifying favorable genes of the East Asian species for future breeding.